THE USE OF SOCIAL MEDIA IN ISLAMIC PREACHING: A CASE STUDY OF THE YOUTUBE CHANNEL OF ASH-SHOMAD MOSQUE - Idi Pangestu (Sekolah TInggi Ilmu Dakwa dan Komunikasi Islam (STIDKIS) Al Mardliyyah Pamekasa, 2025)
The shift from traditional media such as newspapers, magazines, and television to digital platforms, including YouTube, has prompted Islamic preaching (dakwah) to adapt to modern technology. In this context, Ash-Shomad Mosque utilizes social media to disseminate Islamic messages to a community that increasingly accesses information online. The objectives of this study are: 1) to examine how the YouTube channel of Ash-Shomad Mosque is used as a medium for dakwah, and 2) to identify the challenges and obstacles present in the operation of the mosque’s YouTube channel. This study employs qualitative field research methods, focusing on the implementation of Ash-Shomad Mosque’s YouTube channel in the development of dakwah media. Data were collected through interviews, observation, and documentation. The object of this research is Ash-Shomad Mosque, Citra Raya, Tangerang. The results indicate that the use of YouTube as a dakwah medium by Ash-Shomad Mosque has had a significant positive impact, both spiritually and socially. Materials such as sermons, Islamic studies, and Friday khutbahs are accessible at any time, allowing worshippers who cannot attend in person to benefit from the teachings. This also supports the dissemination of Islamic values that are inclusive and tolerant. One of the main outcomes is the effective digital dakwah, which enables the mosque to reach audiences beyond the local Citra Raya community, even globally, without geographical limitations.